Designing waveform-processing circuits - Feucht, Dennis (Feucht, Dennis. Analog circuit design series ;, 2010)
"The Analog Circuit Design set reduces the concepts of analog electronics to their simplest, most obvious form which can easily be applied (even quantitatively) with minimal effort. The emphasis of the set is to help you intuitively learn through inspection how circuits work and apply the same techniques to circuits of the same class. The fourth volume in the set Waveform-Processing Circuits builds on the previous 3 volumes (9781891121869; 9781891121838; 9781891121845) and presents a variety of analog non-amplifier circuits, including voltage references, current sources, filters, hysteresis switches and oscilloscope trigger and sweep circuitry, function generation, absolute-value circuits, and peak detectors. Digitizing (ADCs and DACs) and sampling (including some switched-capacitor) circuits are explained, with theory required for design. Sampling theory is developed from both a frequency and time-domain viewpoint, with emphasis upon application to design."--Publisher's website